The Anaphylactoid Constituents in Xue-Sai-Tong Injection - Xiang, Zheng; Qiao, Tie; Xiao, Hang; Kang, Ting-Guo; Dou, Deqiang; Li, Haibo; Kuang, Haixue (Planta Medica, 2013)
Xue-Sai-Tong injection, a traditional Chinese medicine with total saponins of Sanqi ginseng as active ingredients, has been used for more than 500 years to treat coronary artery disease in China. Anaphylactoid reaction induced by Xue-Sai-Tong injection was one of the main adverse drug reactions which has occurred frequently in recent years. It is of importance to elucidate its anaphylactoid constituents. The in vivo anaphyalctoid tests indicated that the anaphylactoid mediators could be used as indexes to evaluate the anaphylactoid action. Further, the in vitro model based on determining the mediators release from the degranulation of mast cells and RBL-2H3 cells stimulated by Xue-Sai-Tong injection was explored. Mediators released from mast cells and RBL-2H3 cells caused by Xue-Sai-Tong injection were determined by comparison of the methods of fluorospectrophotometry, ELISA, and spectrophotometry, respectively, revealing that the histamine release induced by the Xue-Sai-Tong injection could not be assayed accurately by the method of fluorospectrophotometry because of the interference of saponins and unknown components in the injection. The rat peritoneal mast cell was also not an optimal cell model for determining histamine and β-hexosaminidase release due to the higher spontaneous release ratio during the cell collection. Thus, ELISA determination of the histamine release from RBL-2H3 cells is a suitable in vitro model to assay the anaphylactoid reaction of Xue-Sai-Tong injection. Previously, abnormal hemolysis in some batches of Xue-Sai-Tong injection was observed in the course of their HD50 (half hemolytic dosage) determination. This study further found that injections which exhibited an abnormal hemolysis phenomenon also caused a higher release of the anaphylactoid mediators from RBL-2H3 cells, indicating the HD50 could be an auxiliary index to evaluate anaphylactoid action of the herbal injection indirectly. Research for anaphylactoid components in Xue-Sai-Tong injection indicated that proteins with over 10 KDa of molecular weight, but not ginsenosides, could be the main constituents inducing the release of anaphylactoid mediators from RBL-2H3 cells. An HPLC method for protein determination in the Xue-Sai-Tong injection was established subsequently, and the content of proteins with molecular weights of over 10 KDa in the injections showed an obviously positive correlation with the histamine release induced by the injections. In addition, taking ginsenoside-Rd coupled with BSA as an example, the hapten property of ginsenosides was studied and the ratio of ginsenoside-Rd to BSA was determined to be 8 : 1 by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, and the ginsenoside-BSA conjugate showed a stronger action to stimulate histamine release from the RBL-2H3 cells.
Keywords: herbal medicine injection; anaphylactoid reaction; Panax notoginseng; ginsenoside; RBL-2H3 cells; histamine; Araliaceae